Literature Review: Hubungan Pengetahuan terhadap Sikap Masyarakat tentang Upaya Pencegahan Penularan Tuberculosis - Fitriani Ningsih; Riska Ovany; Yuni Anjelina (Jurnal Surya Medika (JSM), 2022)
Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis. Tuberculosis is still a global public health problem that is a global challenge. One of the causes of the lack of public knowledge in efforts to prevent the transmission of Tuberculosis is the lack of information and education from health workers cadres about Tuberculosis, resulting in a lack of public knowledge about Tuberculosis. This study aims to explain " Correlation Between Knowledge Level And Attitude Of The Community About The Prevention Of Transmission Of Lung Tuberculosis" based on data through the Literature Review method. Using the Literature Review method. Journal searches use an academic database, namely Google Scholar which was published in 2017-2020 using Indonesian and English. Cross-sectional study design. Of the 6 journals, there are 3 journals that state that there is a relationship between knowledge and public attitudes about efforts to prevent Tuberculosis transmission with a p-value = 0.05). while 3 journals state that there is no relationship between knowledge and efforts to prevent Tuberculosis there is a relationship between attitudes and Tuberculosis prevention efforts. One of the causes of the lack of public knowledge in efforts to prevent the transmission of Tuberculosis is the lack of information and education from health workers or posyandu cadres about Tuberculosis, causing a lack of public knowledge about Tuberculosis. Other factors that can influence a person's attitude such as family, the influence of friends, personal experience, and information obtained from various sources.